What is sex? - Zupančič, Alenka 1966- (MIT Press, 2017)
Consider sublimation - conventionally understood as a substitute satisfaction for missing sexual satisfaction. But what if, as Lacan claims, we can get exactly the same satisfaction that we get from sex from talking (or writing, painting, praying, or other activities)? The point is not to explain the satisfaction from talking by pointing to its sexual origin, but that the satisfaction from talking is itself sexual. The satisfaction from talking contains a key to sexual satisfaction (and not the other way around) - even a key to sexuality itself and its inherent contradictions. Zupani argues that sexuality is at the point of a "short circuit" between ontology and epistemology. Sexuality and knowledge are structured around a fundamental negativity, which unites them at the point of the unconscious. The unconscious (as linked to sexuality) is the concept of an inherent link between being and knowledge in their very negativity.
Includes bibliographical references
Keywords: Philosophie; Psychoanalyse; Sex (Psychology); Psychoanalysis -- Philosophy; Sex -- Philosophy; Sexualverhalten